Characteristics associated with clinical severity and inflammatory phenotype of naturally occurring virus-induced exacerbations of asthma in adults. (February 2017) - Bjerregaard, Asger; Laing, Ingrid A.; Poulsen, Nadia; Backer, Vibeke; Sverrild, Asger; Fally, Markus; Khoo, Siew-Kim; Barrett, Lucy; Baltic, Svetlana; Thompson, Philip J.; Chidlow, Glenys; Sikazwe, Chisha; et al.
Abstract: Background: In experimental studies viral infections have been shown to induce type 2 inflammation in asthmatics, but whether this is a feature of naturally occurring virus-induced asthma exacerbations is unknown. Thymic stromal lymphopoietin (TSLP) released from the airway epithelium in response to damage, has been suggested as a link between viral infection and type 2 inflammation, but the role of TSLP in asthma exacerbations is unknown. Objective: To assess whether type 2 inflammation, as measured by sputum eosinophils and fractional exhaled nitric oxide (FeNO), is a feature of naturally occurring virus-induced exacerbations of asthma and whether TSLP is associated with this type 2 inflammation. Methods: Patients presenting to hospital with acute asthma were examined during the exacerbation, and after 4 weeks recovery. The assessments included spirometry, FeNO and induced sputum for differential counts and TSLP mRNA levels. Nasal swabs were collected for viral detection. Results: Sputum eosinophils and FeNO were similar between virus-positive (n = 44) and negative patients (n = 44). In virus-positive patients, TSLP expression was lower at exacerbation than follow-up (p = 0.03). High TSLP at exacerbation was associated with lower sputum eosinophils (p = 0.01) and higher FEV1 (p = 0.03). In virus-positive patients, %-predicted FEV1 negatively correlated with both FeNO and sputum eosinophils (p = 0.02 and p = 0.05, respectively). Conclusion: Our findings support that type 2 inflammation is present in patients during virus-induced asthma exacerbations, to the same degree as non-viral exacerbations, and correlate negatively with FEV1. However, in virus-positive patients, high TSLP expression during exacerbation was associated with low sputum eosinophils, suggesting that the effect of TSLP in vivo, in the setting of an asthma exacerbation, might be different than the type 2 inducing effects observed in experimental studies. Highlights: Sputum eosinophils and FeNO are similar in virus-induced and non-viral exacerbations. Sputum eosinophils and FeNO correlate with FEV1 during exacerbation. TSLP correlate negatively with sputum eosinophils during virus-induced exacerbations.